ABOUT THE INFLUENCE OF A ZEOLITE CONTAINING FILLER (NATROLITE) ON THE PROPERTIES OF CEMENT BINDER - Мakhamadaziz Rasulmukhamedov; Ilkhom Kadyrov; Doniyor Davronov (International Engineering Journal For Research & Development, 2021)
The research paper of the influence of the zeolite-containing filler of the Beltau field on the properties of the cement binder. The results of the experiment of the influence of dispersity and degree of filling on the strength of cement stone are graphically presented. The data obtained confirm the feasibility of using this type of filler in concrete.